INSTRUMEN ASESMEN AUTENTIK MENULIS TEKS FAKTUAL UNTUK SISWA KELAS IV - Titis Angga Rini; Titik Harsiati; Imam Agus Basuki (Pascasarjana Universitas Negeri Malang, 2017)
The assessment instruments have an important role to support process of authentic assessing student learning. The result of needs analysis show that there is a lack of writing assessment instruments used in primary school. The purpose of this research is to develop authentic original text writing assessment instruments for elementary school students. This research adapted the assessment development model from O'Malley & Pierce (1996). This development research produces factual writing assignments for students with assessment rubrics, and a grading guide for teachers. This product is eligible in terms of validity, reliability, legibility, and practicality as a means of writing assessment. Instrumen asesmen autentik berperan penting untuk menunjang proses asesmen pembelajaran siswa di sekolah. Hasil analisis kebutuhan menunjukkan bahwa terdapat keterbatasan instrumen asesmen menulis yang digunakan di SD. Tujuan penelitian ini adalah untuk mengembangkan instrumen asesmen autentik menulis teks faktual untuk siswa kelas IV. Penelitian pengembangan ini mengadaptasi model pengembangan asesmen autentik O'Malley & Pierce (1996). Penelitian pengembangan ini menghasilkan produk yang terdiri atas buku tugas menulis teks faktual untuk siswa dengan rubrik penilaiannya dan buku panduan asesmen untuk guru yang layak dari segi validitas, reliabilitas, keterbacaan, penyajian, dan kepraktisan sebagai instrumen asesmen autentik menulis.